1994
DOI: 10.1111/j.1365-2958.1994.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ribosomal proteins during growth of Streptomyces coelicolor

Abstract: Changes in expression of ribosomal protein genes during growth and stationary phase of Streptomyces coelicolor A3(2) in liquid medium were studied. Proteins being synthesized were pulse-labelled with [35S]-methionine, separated by two-dimensional polyacrylamide gel electrophoresis, and quantified using the BioImage computer software. Most of the ribosomal proteins were synthesized throughout the life cycle. Exceptions were two proteins whose synthesis drastically decreased at the approach of stationary phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 52 publications
2
32
2
1
Order By: Relevance
“…This growth arrest precedes antibiotic production (28) and can activate antibiotic biosynthetic genes (31,43), antibiotic resistance genes (50), and stress response stimulons (48), as well as arrest of ribosomal protein synthesis (3). In this work, we demonstrate that this growth arrest corresponds to the transition phase from the first vegetative compartmentalized mycelium to the second multinucleated differentiated mycelium, which is the one which produces antibiotics.…”
Section: Discussionmentioning
confidence: 88%
“…This growth arrest precedes antibiotic production (28) and can activate antibiotic biosynthetic genes (31,43), antibiotic resistance genes (50), and stress response stimulons (48), as well as arrest of ribosomal protein synthesis (3). In this work, we demonstrate that this growth arrest corresponds to the transition phase from the first vegetative compartmentalized mycelium to the second multinucleated differentiated mycelium, which is the one which produces antibiotics.…”
Section: Discussionmentioning
confidence: 88%
“…1), suggesting that considerable heterogeneity is present in these GC-rich genomes. The genes encoding ribosomal proteins, which are expected to be expressed at high levels during rapid cell growth in Streptomyces (Blanco et al, 1994), were identified and are highlighted in the N c plots. The clustering of most of the ribosomal protein genes of the two Streptomyces genomes at low ends is similar to that in the GC3s versus N c plot of the E. coli genome (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Important aspects of primary metabolism, such as the machinery involved in protein synthesis, have not been studied in such great detail. Dierences in the ribosomal protein pattern among several streptomycete species have been described (Fierro et al 1987;Ochi 1992) and changes in the pattern of ribosomal proteins during spore germination (Mikulik et al 1984;Quiro s et al 1989) and during the transition from substrate to aerial mycelium (Quiro s et al 1992;Blanco et al 1994) have also been noted. Only a few genes encoding Streptomyces ribosomal proteins have been cloned and sequenced and they correspond to only a few operons: the L11 and L10 operons (Blanco et al 1992(Blanco et al , 1994Parra et al 1992;Ruengjitchawalya et al 1993;Katayama et al 1996), the L34 operon (Calcutt and Schmidt 1992), the spc operon (Hale et al 1995) and the alpha operon (Cho et al 1996).…”
Section: Introductionmentioning
confidence: 95%